A container dispatching system for river ports based on distributed intelligent agent - Jingyuan Zeng; Zhenji Zhang; Xiaolan Guan; Ruize Gao (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: With the expansion of business scope of river ports, it demands higher loading and unloading efficiency. Automation, informatization and intellectualization become the only way to development of river ports. Because the key process in river port is container dispatching, the purpose of this paper is to design a container dispatching system, which can improve port performance. Design/methodology/approach: At first, this paper establishes an informatization framework for river ports to discuss and clarify the importance of the container dispatching system in informatization of river ports. And then, the system structure is designed based on distributed business intelligence. It contains four levels, data source layer, data warehouse layer, data service layer and application layer. The main modules are discussed in detail. At last, a KPI model is established to appraise the performance of this system. Findings and Originality/value: This paper develops an original container dispatching system based on distributed business intelligence. Through performance comparison and analysis before and after the system implementation in Whampoa, the system is proved to have a lot of real benefits: with the system, the resource utilization rate is improved and profitless operation and the cost are reduced; the system reduces the labor intensity and labor cost and optimizes the configuration of personnel; the system helps on dynamic decision-making; it provides a way for real-time data interchange with government regulators and customers so that extended, personalized and interactive service can be realized.
Keywords: 650; container dispatching system; port planning; storage optimization; business intelligence